Ecosystem Services Assessment of Mangrove Forest in a Coastal Island of Bangladesh - Al Mamun, M. M Abdullah; Shimu, Shakhera Akter; Sarker, A. H. M Raihan; Masum, Kazi Mohammad (Journal of Forests, 2021)
Using the Department for Environment, Food, and Rural Affairs of UK (DEFRA) framework, all the ecosystem services from the Hatiya coastal forest under the Noakhali Coastal Forest Division of Bangladesh have been listed down to prepare a considerable record for valuing ecosystem services. Different valuation assessment techniques like market price method, travel cost method, Contingent Valuation Method (CVM) have been used to calculate timber, fish, and tourism values. Following the allometric equation, the sequestrated biomass carbon has been estimated. This study has evaluated the economic values of different ecosystem services in Hatiya coastal forests, including timber value of 32year aged old plantation as 303,040.50 thousand USD, annual fish catch amount as 61.5 thousand metric ton (MT) price with 115,217.25 thousand USD, the value of newly accreted land 22,239.46 thousand USD of 6000 ha, annual tourism value of 114.90 thousand USD and the willingness to pay by the tourists as 6.06 thousand USD. The study also estimated the total stored carbon amount by biomass and soil of the area as 252304.67 ton and 1365642.098 ton, respectively. In addition, using the GIS tool, the Land-use and Land-cover (LULC) change has been assessed to show the mangrove area condition comparing with previous years. This study aims to be a preliminary source for valuing ecosystem services further in Hatiya and other coastal forests, which will drive the policymakers to take appropriate and realistic initiatives for sustainable management of coastal forests as well as allocate budget for the forestry sector during national planning.